Kajian sakit belakang dan faktor-faktor yang mempengaruhinya di kalangan pekerja pemasangan industri automotif - Anuar I; Nurulakhmar AS; Mazrura S; Azhar AH (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2010)
Back pain associated with sense of pain and less comfort in back part of the body especially at the lower back area. Back pain is an occupational health problem with significant impact to productivity of workers. Methodology : A cross sectional study was conducted to study the prevalence of back pain towards individual, physical and psychosocial factors associated among body shop’s operators at national Automotive Manufacturers. Result : A total of 32 operators were involved in this study. Nordic Musculoskeletal questionnaire has been used in this study and body position assessment was done by using Ovako Working Posture Analyzing System (OWAS) method. Study showed the prevalence of back pain among operators throughout their work and in the last 12 months was 93.8% and 87.5% respectively. There are significant association (p<0.05) between drilling activity and bending forward. However, there was no significant association (p>0.05) between prevalence of back pain with another individual, physical and psychosocial factor. Conclusion : This study shows that back pain prevalence were influenced by types of activity and body posture during working at assembling division among workers. Attention should be given to ergonomics factors to prevent back pain incident among automotive industry assembly workers.